PENGARUH MEDIA PEMBELAJARAN GOOGLE CLASSROOM PADA PEMBELAJARAN MATEMATIKA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VII DI SMPN 1 AMPEK ANGKEK KABUPATEN AGAM - Muhammad Ilham (Departemen Matematika, 2022)
SMPN 1 Ampek Angkek is one of the new schools use Online learning in the COVID-19 pandemic. One of the efforts to improve student learning during the COVID-19 pandemic is to apply mathematics learning using Google Classroom media. The purpose of the study was to determine and analyze the effect of Google Classroom learning media on mathematics learning on the learning outcomes of class VII SMPN 1, Ampek Angkek, Agam Regency. This type of research is quasi-experimental. The population is class VII SMPN 1 Ampek Angkek for the academic year 2021/2022. Sampling was done by a simple random sampling technique. The number of students in the experimental and control classes amounted to 31 and 32 people, respectively. The data analysis technique was carried out by the t-test. Based on the results of data analysis, it was determined that P-value = 0.002, so H0 was rejected and H1 was accepted because 0.002 0.05 indicates that there is an effect of using Google Classroom media on Online mathematics learning. Keywords– Learning Media in Google Classroom, Mathematics Learning, and Learning Outcomes